Central nervous system physiology. Issue 12 (December 2021) - Rothwell, John; Antal, Andrea; Burke, David; Carlsen, Antony; Georgiev, Dejan; Jahanshahi, Marjan; Sternad, Dagmar; Valls-Solé, Josep; Ziemann, Ulf
Highlights: This review is the second in the series of articles on the use of clinical neurophysiology for the study of movement disorders. It focuses on the most useful non-invasive methods and techniques that can probe the neurophysiology of the central nervous system in humans. Tools include reflex studies, transcranial brain stimulation, electroencephalography and reaction times. Abstract: This is the second chapter of the series on the use of clinical neurophysiology for the study of movement disorders. It focusses on methods that can be used to probe neural circuits in brain and spinal cord. These include use of spinal and supraspinal reflexes to probe the integrity of transmission in specific pathways; transcranial methods of brain stimulation such as transcranial magnetic stimulation and transcranial direct current stimulation, which activate or modulate (respectively) the activity of populations of central neurones; EEG methods, both in conjunction with brain stimulation or with behavioural measures that record the activity of populations of central neurones; and pure behavioural measures that allow us to build conceptual models of motor control. The methods are discussed mainly in relation to work on healthy individuals. Later chapters will focus specifically on changes caused by pathology.